The Effect of the Methods of Distributed and Intensive Exercise in Terms of Mental Logic in Learning Some of the Basic Skills of Futsal - Yasin Ali Khalaf (Journal of Global Pharma Technology, 2018)
The research aims to study the effect of using the distributed and intensive exercise in terms of mental logic in learning some basic skills of futsal, and to compare the effect of the use of the distributed and intensive exercise in the sense of mental reasoning in the remote tests in learning some basic skills of futsal. The researcher used the experimental method to suit the nature of the research. The research society was chosen deliberately by the students of the second stage in the Faculty of Physical Education - University of Sulaymaniyah for the academic year 2016-2017 (32) students, where the percentage of the sample (75%) of the community of origin, 24 students were divided into two experimental groups with 12 students per group. Eight students were excluded from the pilot experiment. By the draw, the first experimental group was chosen to implement the distributed method while the second group performed the intensive method. The results of the tests were statistically treated and the researcher concluded that the experimental groups achieved progress using the methods of the distributed and intensive training in the sense of mental reasoning to learn some basic skills of futsal halls, and the results showed that the superiority of the first experimental group T-used style exercise distributor on the second experimental group that used the style of intensive exercise in their results dimensionality.Keywords: Methods, Distributed and intensive exercise, Mental logic and futsal.